2021
DOI: 10.3390/molecules26247565
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Metabolomics Approach in Food Authentication

Abstract: The authentication of food products is essential for food quality and safety. Authenticity assessments are important to ensure that the ingredients or contents of food products are legitimate and safe to consume. The metabolomics approach is an essential technique that can be utilized for authentication purposes. This study aimed to summarize food authentication through the metabolomics approach, to study the existing analytical methods, instruments, and statistical methods applied in food authentication, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 100 publications
1
26
0
Order By: Relevance
“…These nitrogen isotope ratios were in the range of those from previous studies conducted in the Jeonnam regions (Hwayang, Dolsan, and Jinahae) [19]. The differences observed the in Jeonbuk, Jeonnam, and Gyeongnam regions suggested that the river discharge causing the inflow of different DIN concentrations by season might have produced the 15 N-enriched isotopic signature in clams [47].…”
Section: First Step: a Dual-isotope Analysis For Distinct Geographica...supporting
confidence: 55%
See 2 more Smart Citations
“…These nitrogen isotope ratios were in the range of those from previous studies conducted in the Jeonnam regions (Hwayang, Dolsan, and Jinahae) [19]. The differences observed the in Jeonbuk, Jeonnam, and Gyeongnam regions suggested that the river discharge causing the inflow of different DIN concentrations by season might have produced the 15 N-enriched isotopic signature in clams [47].…”
Section: First Step: a Dual-isotope Analysis For Distinct Geographica...supporting
confidence: 55%
“…The increasing demand for traceability has led to various studies that have presented scientific evidence for some techniques as well as for national policies [4,7]. For agricultural products, dairy products, and processed foods, such as oil and wine, reliable results have been reported for several approaches using stable isotopes, DNA, metabolomics, and microbiological information [14,15]. For example, stable isotope analysis (SIA) is an effective method for determining environmental information, habitat, and ecosystem-based diets [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics has been developed and applied in many research areas and is becoming the most active field of investigation among omics techniques because metabolomics could be used to represent phenotype. In recent years, the utilization of metabolomics in food science, and specifically in food authentication, has gradually increased to address some issues related to food adulterations, food origins, and food contamination [15].…”
Section: Metabolomics For Non-halal Meats' Analysismentioning
confidence: 99%
“…Proper plant development depends on their presence and concentration. Metabolomics enabled the systematic study of metabolites and their interactions [ 15 ]. Metabolomics studies were successfully applied in pharmaceutical, biomedical, agricultural and nutritional sciences, including drug discovery, disease diagnosis and plant phenomena [ 16 ].…”
Section: Introductionmentioning
confidence: 99%